Attitudes of Lagos Residents to waste disposal as major causes to yearly flooding (Journal of Basic and Applied Research in Biomedicine, 2022)
This paper highlights the attitudes of Lagos residents to waste disposal as the major causes to yearly flooding in the city. It also presents data from an evaluation study of environmental sanitation in six communities spread across three Local Government Areas (LGAs) in Lagos State. The data were analysed descriptively using simple percentages. The paper shows that house hold levels seem to be the best way to start addressing the twin issues of waste disposal and flood control in Nigerian cities. The major findings regarding waste disposal relate to vendors, LAWMA, dumping inside gutters and burning. It therefore suggests result/task oriented use of household resources at the community level to tackle the hydra headed problem of waste disposal and thereby control annual floods that maroon Lagos city yearly. Further still, the expected responsibilities of the Household/ Community, Local Government Areas and the State levels in reshaping the attitudes of people at each level are discussed in the paper. By way of conclusion, the need to incorporate this approach into physical planning in the urban areas is highlighted in the paper.